2018
DOI: 10.1371/journal.pone.0207762
|View full text |Cite
|
Sign up to set email alerts
|

Timberline structure and woody taxa regeneration towards treeline along latitudinal gradients in Khangchendzonga National Park, Eastern Himalaya

Abstract: With main purpose of developing a coherent baseline information of timberline forests of Sikkim, Eastern Himalaya, we investigated, (i) forest structure and composition, (ii) regeneration status of dominant timberline tree species between timberline and treeline, (iii) influence of environmental variables in species composition, and (iv) relationship between environmental variables and ecological attributes. The study was conducted along the timberline stretch of Dzongri landscape nested within the Khangchendz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…The regeneration of the plant is the key ecological process in a forest ecosystem in which seeding and sprouting of woody species are involved (Pratt et al 2012). One of the most important problems that mountainous forests are experiencing is poor regeneration (Karauchi et al 2000), which is especially observed in subalpine forests in Eastern Himalaya (Tambe et al 2011;Pandey et al 2018) as well as in Western Himalaya (Rai et al 2012). Poor regeneration and naturally slow growing nature of Larix griffithiana are documented in subalpine forests in Sikkim Himalaya (Tambe et al 2011) and absence of seedlings and saplings of the species has been recorded in temperate forests in Lachung Range of the Sikkim Himalaya (Subba et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regeneration of the plant is the key ecological process in a forest ecosystem in which seeding and sprouting of woody species are involved (Pratt et al 2012). One of the most important problems that mountainous forests are experiencing is poor regeneration (Karauchi et al 2000), which is especially observed in subalpine forests in Eastern Himalaya (Tambe et al 2011;Pandey et al 2018) as well as in Western Himalaya (Rai et al 2012). Poor regeneration and naturally slow growing nature of Larix griffithiana are documented in subalpine forests in Sikkim Himalaya (Tambe et al 2011) and absence of seedlings and saplings of the species has been recorded in temperate forests in Lachung Range of the Sikkim Himalaya (Subba et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Sustainability of populations with inadequate number or lack of regenerating individuals has been reported to be challenging for several species of subalpine trees. Examples include Larix potaninii in China (Taylor et al 1996;Cui et al 2017;Liang and Wei 2020), Larix griffithiana in Sikkim, India (Tambe et al 2011;Subba et al 2015), and Bhutan (Moktan 2010); and for many other species in the eastern Himalaya (Pandey et al 2018), Nepal Himalaya (Vetaas 2000;Shrestha et al 2007;Kunwar 2011;Sujakhu et al 2013;Maren et al 2015;Suwal et al 2016), and western Himalaya (Rai et al 2012). Therefore, for the effective conservation of the typical Himalayan vegetation of Larix forests, efforts need to be concentrated both locally and regionally.…”
Section: Parametermentioning
confidence: 99%
“…In resent years, more and more researches explained the correlation between tree community's crown volume and elevation [7]- [13]. These researches include dynamics of community's crown volume traits [1], tree community's crown volume structure [2], tree community's crown volume growth [3] [4] [5], tree leaf structure of community's crown volume [6], community canopy crown volume and structure [7]- [11] along elevation gradient. Thus, the results indicate that elevation was the dominant environment driver of crown volume of 18 (Sophora japonica) tree communities increased along elevation gradient.…”
Section: Discussionmentioning
confidence: 99%
“…The correlations between tree community's structure and elevation include tree community traits [1], tree community structure [2], tree community growth [3], DOI: 10.4236/oje.2019.97017 210 Open Journal of Ecology tropical tree community growth [4], tree community [5], tree community's leaf structure [6], and community canopy structure [7] in the environmental (size-dependent changes [1], latitudinal [2], climate warming [3], elevation [4], climate variations [5], ecological environment [6] [7]) dynamics along elevation in the forestry ecosystems. However, there is the correlation between crown volume of (Sophora japonica) tree communities and elevation along elevation gradient in Ye County.…”
Section: Introductionmentioning
confidence: 99%
“…Climate warming is critically viewed in response to the loss of alpine biodiversity (Gentili et al, 2015). In mountain regions, upward movements of plant species and timberlines are predicted to reach «sky islands» (Gottfried et al, 2012;Pandey et al, 2018). The increase in mean annual temperatures is not uniform around the globe.…”
Section: Introductionmentioning
confidence: 99%